Futility and Patients Who Insist on Medically Ineffective Therapy - Cifrese, Laura; Rincon, Fred (Seminars in Neurology, 2018)
As medical decisions fall under more scrutiny and society demands increasing transparency of care, it is likely that more opportunities for conflicts will emerge. Similarly, with increasing demand and a static supply, the issue of who receives treatment and for how long naturally will arise. This mismatch leads to discussions of resource utilization and limitation of care in light of patients' values and rights. Clinicians should always be forthcoming with the uncertainty of prognostication while also articulating the severity of a patient's disease in relation to the risk and benefits of an intervention. However, dispute over treatment course and the idea of futile care can arise for in a variety of reasons, both from the clinician and the patient. Without identifying the cause of these conflicts, it is impossible to have effective communication. At times, it is important to utilize various negotiating skills when resolving these disagreements. Regardless of the approach, practitioners need more training in and exposure to these types of conflicts. In this review, we provide a framework for the origins and current state of futility, challenges in the application of the term, and recommendations on how to approach conflict in these situations.
Keywords: ethics; morality; end-of-life; inappropriate treatment